Мodel of training future teachers of technologies to using the computer technics in the process of studing professional disciplines (Pedagogy of Higher and Secondary Education, 2012)
Tereshchenko S. Мodel of training future teachers of technologies to using the computer technics in the process of studing professional disciplines.The article deals with the problem of using the computer technics by the future teachers of technologies in the process of studying of specialized disciplines, it is defined the model of training future teachers of technologies to using the computer technics.
Keywords: computer technics; model of training future teachers of technologies